Digital populism in political communication research: A systematic literature review and bibliometric analysis (2015-2025) - Ryan Taufika; Karim Suryadi; Cecep Darmawan; Asep Mahfudz (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This study investigates the development of digital populism in political communication research through a Systematic Literature Review (SLR) and a bibliometric analysis of the Scopus database. Using the PRISMA screening framework, 18 relevant journal articles published between 2015 and 2025 were identified, suggesting that although research in this field remains limited, it has shown a notable increase, particularly after 2021. The findings indicate that the concept of digital populism has evolved from an initial focus on online activism and networked resistance to a more comprehensive framework that explains how populist messages are strategically created, distributed, and amplified through digital platforms and their underlying logics. Bibliometric mapping reveals key thematic clusters of digital populism, nationalism, and populism, with discourse analysis as the dominant methodological approach. Furthermore, the synthesis highlights five defining characteristics of digital populism: people-centrism, emotional communication, political visualisation, virality, and direct participation. Despite these insights, the literature remains heavily concentrated in Western contexts, with limited contributions from Asia and the Global South. Accordingly, future studies should broaden data sources and pursue comparative research across diverse sociopolitical contexts to enhance theoretical and empirical understanding.